PATHOLOGICAL BLOOD CHANGES IN SYSTEMIC LUPUS ERYTHEMATOSUS - Egamova S.Sh; Iskanova G.Kh; Karimdzhanov I.A (Scholar Express Journals, 2023)
The article describes the features of the course of systemic lupus erythematosus in patients with anemia of chronic diseases, iron deficiency anemia and autoimmune hemolytic anemia. Patients from 18 to 60 years old with varying degrees of disease activity were examined. Various examination methods used to diagnose systemic lupus erythematosus as an autoimmune disease are reviewed, some of these methods include (complete blood count, serum iron, hematocrit, etc.). In addition, the pathological mechanism of anemic syndrome in systemic lupus erythematosus is discussed.
Keywords: systemic lupus erythematosus; anemia of chronic diseases; iron; hemoglobin